Proyecto de factibilidad para la implementación de una planta procesadora de balanceado de crecimiento, para aves (pollos) en el cantón Zapotillo, provincia de Loja 2021 - Morillo Jumbo, Erika Jamilex (2023)
The main objective of this research work is to determine the feasibility for the implementation of a poultry (chicken) growth balance processing plant in the Zapotillo canton, province of Loja, 2021. In order to achieve the objectives, the following studies were carried out to determine the feasibility of the project. The feasibility project has a descriptive research of which bibliographic compilation techniques and surveys were designed for the plaintiffs and suppliers, through the determination of a sample of 342 surveys directed to the families of the Zapotillo canton, which allowed gathering relevant information for the present project. This made it possible to conduct the market study, obtaining an unsatisfied demand of 5,325 quintals of balanced feed in the first year; in addition, a business plan was developed to introduce the new product to the market. The technical study analyzed that the installed capacity is 13,140 quintals of feed and the capacity used is 2,259 quintals; the macro and micro location to determine the location of the company, and will be located in the Zapotillo canton, on the land of Mr. Brayan Javier Coronel. The investment amounts to $38,554.32, which can be financed by the company's partners and a loan. The financial indicators show an NPV of 6,633.94; an IRR of 17.95%; the investment is recovered in 4 years, 6 months and 20 days; the benefit-cost ratio is 0.14 dollars; if the cost of production increases by 3% and income decreases by 3%, the project is still profitable. If implemented, the project would constitute a fundamental pillar for the socioeconomic development of the Zapotillo canton.